Ibn Hazm's views of language acquisition in the light of 'Ilm al-Kalam : a critical study - Al-Sabahi, Samira Mohammed Ali (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2012)
This work studies the theory of language acquisition according to Ibn Hazm by applying Ilm al-Kalam as a methodology. As such, the study examines the Muslim scientific approach to studying linguistics, in general, and language acquisition, in particular. Additionally, the study also investigates Ibn Hazm's intellectual environment in Andalusia along with the social and political surrounding that formed his views. It adopts a qualitative approach that depends on an array of classical and modern books from both the Muslim and Western worlds. A great number of diverse opinions are presented. Moreover, this work sheds light on the Arabic language before and after the emergence of Islam and its influence on the development of the Islamic sciences such as Fiqh, Hadith and Ilm al-Kalam. It gives a brief summary on the achievements of Muslim scholars in the field of linguistics. It also examines the theories of other scholars and opinions on language acquisition. The work discusses closely the significance of ancient civilizations such as the Greek, the Persian and the Athenian, and their influence on the progress of philosophy and Ilm al-Kalam. The study checks the modern theories of language acquisition against that of Ibn Hazm's in order to connect the scientific approach of Muslim scholars to that of modernists. In addition, this work also inspects closely the unique use of scientific methodology of Muslim scholars in combining the Divine knowledge with that of this world.